Selection and Endogenous Treatment Models with Social Interactions: An Application to the Impact of Exercise on Self-Esteem - Zhongjian Lin; Francis Vella (Institute of Labor Economics (IZA), 2021)
We address the estimation of sample selection and endogenous treatment models with social interactions. To model the interaction between individuals in an internally consistent matter we employ a game theoretic approach based on the use of a discrete Bayesian game. We overcome the substantial computational burden this introduces through a sequential version of the nested fixed point algorithm. We describe how our methodology can be applied to a large class of commonly employed models. We employ our approach to examine the impact of an individual's frequency of exercise on her level of self esteem in a setting where an individual's exercise frequency is treated as endogenous and is potentially influenced by her belief of her friends' exercise frequency.
Keywords: C31; C34; C57; Z2; 330; endogenous treatment; sample selection; social interactions; sequential estimation; exercise; self-esteem